Utilization of mobile surgical units to address surgical needs in remote African communities: a narrative review - Mugisha, Nadine; Uwishema, Olivier; Noureddine, Rawan; Ghanem, Laura; Manoel, Agnes Zanotto; Shariff, Sanobar (BioMed Central Ltd, 2024)
Introduction Accessing surgical care is of profound significance that face remote African communities due to insufficient healthcare means and infrastructure. Deploying mobile surgical units (MSUs) have present a potential solution to underserved populations in rural Africa to address said issues. The aim of this narrative review is to examine the role of MSU utilization in remote African communities to meet surgical needs and evaluate how this has affected healthcare provision. Methods To identify studies focusing on the dissemination of MSUs in remote African communities covered countries such as Uganda, Kenya, Tanzania, Nigeria, and Ethiopia, and we employed a plethora of electronic search databases including PubMed/Medline, Google Scholar, Scopus and other relevant literature sources. Inclusion criteria were studies on MSUs in remote African communities, while exclusion criteria involved non- African or urban-focused studies. Results This review highlights that the current literature depicts that application of MSUs bring a positive impact in providing timely and quality surgical care to remote African communities. Frequent interventions, such as minor surgeries, obstetric procedures, and major trauma control, have been performed on MSUs. In settings with shortages of human resources and clinical equipments, these units have improved patient outcomes, reduced healthcare disparities, and increased access to emergency surgical care. While challenges such as financial constraints and surgical sustainability have been noted, the need for interdisciplinary collaboration and the advantages of MSU deployment often help mitigate these obstacles. Conclusion A lack of surgical care for individuals living in remote African domiciles may be addressed via MSU application. Through delivering fundamental surgical services directly to underserved populations, MSUs may potentially prevent disabilities, save countless lives, and enhance overall health outcomes in African remote communities. To guarantee the long-term feasibility and sustainability of MSU programs in Africa, however, more funding must be allocated to infrastructure, supplies, and relevant education. Keywords: Surgical care, Healthcare, Mobile surgical units, Remote African communities